Exosomes at the crossroads of HIV-1 pathogenesis and therapeutics - Lu, Pengpeng; Lin, Xu; Yang, Wenyi; Li, Junhao (Frontiers in Immunology, 2025)
Despite advances in antiretroviral therapy (ART), human immunodeficiency virus type 1 (HIV-1) remains a global health challenge, with approximately 39 million people infected worldwide, persistent viral reservoirs, and delayed immune reconstitution. Exosomes, which are extracellular vesicles (30–150 nm) that play a key role in intercellular communication, have a dual role in HIV-1 pathogenesis and therapy. Regarding pathogenesis, this review elucidates how HIV-1 exploits the exosome pathway—hijacking the Endosomal Sorting Complex Required for Transport(ESCRT)machinery for viral budding and selectively packaging viral components, such as the accessory protein Nef, to enhance infectivity, promote immune evasion, and establish latent reservoirs. Conversely, host cells utilize exosomes to mount antiviral defense by packaging and transmitting restriction factors, such as APOBEC3G, to recipient cells. Furthermore, exosomal cargo serves as promising biomarkers for disease monitoring, and exosomes themselves are emerging as versatile therapeutic nanocarriers. We highlight that plant-derived exosomes offer unique advantages, including low immunogenicity and high scalability, for delivering next-generation antiviral agents or gene editing tools. In summary, understanding the multifaceted roles of exosomes provides crucial mechanistic insights into HIV-1 pathogenesis and unveils innovative strategies toward a functional cure.